Elements of Engagement in Promoting Social Acceptance of Mobile Augmented Reality Application - Baker, Esraa Jaffar; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In a social context, Mobile Augmented Reality is a type of Augmented Reality which enables users to interact with the augmented environment. However, the degree of engagement and non-distraction of Mobile Augmented Reality has been of major concern to scholars. This is because Mobile Augmented Reality should be a focused, movable and engaged augmented environment which allows users to achieve the desired objectives. Therefore, this paper examines the engagement elements of Mobile Augmented Reality that promote social acceptance among users within the vast literature. These elements will enable Mobile Augmented Reality designers and developers to produce apps that will be able to enhance users’ interest and attractiveness in a fun way. Based on the critical and comprehensive review, there are 22 elements of engagement that have been used by previous researchers in the design of Mobile Augmented Reality apps. The 22 elements include; Aesthetics, Novelty, Usability, Feedback, Motivation, Attention, Perceived Control, Curiosity, Enjoyment, Self-efficacy, Friendliness, Social skill, Endurability, Interest, Immersion, Challenge, Satisfaction, User Autonomy, Improvement, Supportive, Trust and Interaction. This paper argues that the 22 elements are critical in producing an engaging Mobile Augmented Reality app. It is recommended for designers to consider these elements in ensuring that the users will be positively engaged with the Mobile Augmented Reality app.